Altered T-Cell Receptor β-Chain and Lactate Dehydrogenase Are Associated With the Immune Pathogenesis of Biliary Atresia - Ye, Jing; Lai, Dengming; Cao, Dan; Tan, Linhua; Hu, Lei; Zha, Hua; Yang, Jiezuan; Shu, Qiang (Frontiers in Medicine, 2021)
Background: Biliary atresia (BA) is considered to be an autoimmune mediating inflammatory injury. The pathogenesis of BA has been proposed with clonal transformation of T cells expressing analogous T cell receptor β-chain variable regions (TRBV). Methods: The TRBV profile of the peripheral blood mononuclear cells (PBMC) in infants with BA and control infants (healthy donors, HD), respectively, were characterized by using high-throughput sequencing (HTS). The diversity of T cells was analyzed based on the frequency of complementarity-determining region 3 (CDR3) or V(CDR3)J. Moreover, the correlation between absolute lymphocyte count (ALC) and lactate dehydrogenase (LDH) or diversity (clonality) indices, respectively, were analyzed for BA and HD subjects. Results: The diversity indices of CDR3, V(CDR3)J in BA are lower than those in HD subjects, additionally, there are significant different levels of neutrophile, neutrophile /lymphocyte ratio (NLR), and LDH between BA and HD groups. The correlation between ALC and diversity index is significant in HD subjects, but is not for BA subjects. Conversely, the relationship between ALC and LDH is significant in BA subjects, but is not for HD subject. Moreover, twelve CDR3 motifs are deficiency or lower expression in BA compared with that in HD group. Conclusions: Our results demonstrate that the profile of TRBV repertoire is significant different between BA and HD subjects, and suggest the immune imbalance and elevated LDH level are associated with the pathogenesis of BA. Moreover, the values of neutrophile, NLR, and LDH could be used to differential diagnosis of BA.